Unraveling the microstructural heterogeneity and plasticity of Zr50Cu40Al10 bulk metallic glass by nanoindentation. (July 2022) - Tao, K.; Li, F.C.; Liu, Y.H.; Pineda, E.; Song, K.K.; Qiao, J.C.
Highlights: Plastic yielding is affected by the normal stress acting on the shear plane, which is verified by finite element methods. The internal friction coefficient is found to decrease with the increase of concentration of flow defects. The effect of structural state modified by annealing or rejuvenation is rationalized by the flow defects concentration. Under different structural states, the displacement bursts are different, changing from obvious to inapparent serration. The schematic illustrats the correlation between the displacement burst and the shear band size. Abstract: Unraveling the microstructural heterogeneity is an important issue to understand the physical and mechanical properties of metallic glasses. Structural relaxation below the glass transition temperature T g and cold rolling at ambient temperature are effective ways to tune the state within the potential energy landscape of metallic glasses, modifying the microstructural heterogeneity. With the help of nanoindentation technique, by scrutinizing the local reduced modulus and hardness of a typical Zr50 Cu40 Al10 metallic glasses in different energy states (from structural relaxed state to rejuvenated state), we demonstrate that the enhancement of microstructural heterogeneity plays an important role in tailoring the mechanical behavior. The internal friction coefficient is obtained by fitting the experimental load-displacement curves with finite element simulation. It is found that internal friction coefficient decreases with the increase of concentration of flow defects. The stress exponent obtained from the creep stage shows a strong dependence on the structural state of metallic glasses. Effects of structural relaxation and rejuvenation on the structural state are rationalized in terms of the relative flow defects concentration. Finally, the statistics of discrete displacement bursts during the deformation process were probed. We find that the displacement bursts behavior is sensitive to the structural energy state (microstructural heterogeneity). The displacement bursts phenomenon changes from obvious (relaxed state) to unapparent behaviors (rejuvenated state). By given a physical schematic, the correlation between the displacement bursts size and the shear band size in the local plastic zones is well established, which will lead to a deeper understanding of the rejuvenation-induced plasticity of metallic glasses. Graphical abstract: Image, graphical abstract